Coerced Labor in the Cotton Sector: How Global Commodity Prices (Don't) Transmit to the Poor - Alexander M. Danzer; Robert Grundke (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper investigates the economic fortunes of coerced vs. free workers in a global supply chain. To identify the differential treatment of otherwise similar workers we resort to a unique exogenous labor demand shock that affects wages in voluntary and involuntary labor relations differently. We identify the wage pass-through by capitalizing on Tajikistan's geographic variation in the suitability for cotton production combined with a surge in the world market price of cotton in 2010/11 in two types of firms: randomly privatized small farms and not yet privatized parastatal farms, the latter of which command political capital to coerce workers. The expansion in land attributed to cotton production led to increases in labor demand and wages for cotton pickers; however, the price hike benefits only workers on entrepreneurial private farms, whereas coerced workers of parastatal enterprises miss out. The results provide evidence for the political economy of labor coercion and for the dependence of the economic lives of many poor on the competitive structure of local labor markets.
Keywords: J47; J43; F16; O13; Q12; 330; coerced labor; export price; price pass-through; cotton; wage; local labor market; Tajikistan